Penile laceration in a Mangalarga Marchador stallion - Moya-Araujo, Carla Fredrichsen; Mendes, Adriano Felipe; Coneglian, Mariana Marcantonio; Camplesi, Annelise Carla [UNESP]; Marques Araujo, Gustavo Henrique (Pontificia Universidade Catolica do Parana - PUCPR, 2019)
A four-year-old Mangalarga Marchador stallion was treated with a complaint of penile injury at the Clinic School of Veterinary Medicine Unicentro. The owner reported that the animal had injured the penis in smooth wire for two weeks. The horse was treated with benzilpenicillin associated with streptomycin, in addition to anti-inflammatory therapy based on dexamethasone, during three consecutive days, without observing clinical improvement. Physical examination showed intense pain and foreskin edema that made it difficult to expose the penis. Administration of acepromazine (0.05 mg/kg, IV) was required for organ evaluation. The laceration extended from the dorsal to ventral portion of the middle third of the penis body without involvement of the prepuce, being covered by areas of necrosis, foul smell and bleeding. No other clinical changes were detected. There were no changes on the haematological parameters. The horse was hospitalized, and the recommended treatment was administration of flunixin meglumine (1.1 mg/kg, IV, every 24 hours) and omeprazole (2 mg/kg, VO, every 24 hours) for five consecutive days, associated with local dressing. This was preceded by cold shower in the foreskin, followed by massage with DMSO gel and repellent spray around the lesion. The penis was exposed for wound cleaning with gauze soaked in 0.9% NaCl solution followed by application of chlorhexidine (0.7 g/100 mL) ointment, a procedure performed every 12 hours for 45 days. On the second day of treatment the edema was decreased, and after five days the horse already exposed the penis to urinate, with complete healing at the end of the treatment. The horse returned to the reproductive activities on the following breeding season, performing mating without presenting anatomical and physiological alterations.
Laceração peniana em cavalo Mangalarga Marchador
Keywords: Clinical treatment; Equine; Penile lesion